PENDAMPINGAN KADERISASI AMIL ZAKAT DI MASJID BINAAN LEMBAGA AMIL ZAKAT MUHAMMADIYAH (LAZISMU) KOTA MALANG - Hakim, Rahmad (Bulletin of Community Service and Development, 2020)
Purpose of the Study: To provide assistance for the regeneration of amil zakat in the LAZISMU-assisted mosques in Malang in order to realize accountable, professional and on target zakat management. Method: Strengthening insight and assistance related to the following topics: 1) education on the importance of zakat management, 2) amil zakat in managing zakat, 3) creating organizational culture in managing zakat 4) making zakat management posters that are accountable, professional and on target. Main Findings: To assist the regeneration of amil zakat in the LAZISMU assisted mosques in Malang. Applications of this study: To enhance the ability of amil zakat in the mosque built by LAZISMU in Malang. Novelty/Originality of this study: Regeneration of amil zakat in the LAZISMU mosque in Malang in order to realize accountable, professional and on target zakat management.